Epitope Mapping of Antibodies Using a Cell Array–Based Polypeptide Library - Maier, Richard H.; Maier, Christina J.; Rid, Raphaela; Hintner, Helmut; Bauer, Johann W.; Önder, Kamil (Journal of biomolecular screening, 2010)
The authors describe a technique for mapping the epitopes of protein antigens recognized by mono- or polyclonal antibodies. This method is based on a recombinant polypeptide library, expressed in a bacterial expression system, arrayed at high density, and tested on a membrane with automated procedures. The authors analyzed the epitope of a commercially available monoclonal antibody to vitamin D receptor (VDR). About 2300 overlapping VDR peptides were screened on a test array, and a contiguous stretch of 37 amino acids was identified as the epitope. Its authenticity was confirmed by Western blotting and an immunofluorescence competition assay on human skin tissue samples. The authors define the proposed method as a cell-based protein or peptide array that is adaptable to many applications, including epitope mapping of antibodies and autoantibodies, autoantigen detection from patient sera, whole-proteome approaches such as protein-peptide interactions, or selection of monoclonal antibodies from polyclonal sera. The advantages of this method are (a) its ease of protein array production based on well-established bacterial protein/peptide expression procedures; (b) the large number of printable colonies (as many as ~25,000) that can be arrayed per membrane; (c) there is no need for protein purification of recombinantly expressed proteins; (d) DNA, rather than protein, is the starting material to generate the arrays; and (e) its high-throughput and automatable format.